2017
DOI: 10.5005/jp-journals-10036-1133
|View full text |Cite
|
Sign up to set email alerts
|

Epithelial–mesenchymal Transition of Glomerular Podocytes: Implications in Proteinuria

Abstract: The kidneys play an essential role in filtration of blood plasma, regulation of water, electrolyte, and acid/base balance of the body, and thus maintain overall homeostasis. The glomerular filtration barrier serves as a size, shape, and charge barrier to ensue glomerular permselectivity, so that kidneys excrete almost protein-free urine. Podocytes are glomerular visceral epithelial cells and significantly contribute to the glomerular permeability owing to their unique structure and specialized function. Nevert… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 37 publications
(44 reference statements)
0
3
0
Order By: Relevance
“…Glomerular podocytes are instrumental to ensure glomerular permselectivity (Anil Kumar et al, ). It was reported that podocytes undergo EMT and such a glomerular injury with reduced podocyte count was associated with proteinuria (Chitra et al, ; Nishad, Nakuluri, Motrapu, & Pasupulati, ). To investigate whether the observed proteinuria and decreased podocyte count in rats exposed to hypoxia were owing to podocyte injury, we then investigated the effect of hypoxia on human immortalized podocytes.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Glomerular podocytes are instrumental to ensure glomerular permselectivity (Anil Kumar et al, ). It was reported that podocytes undergo EMT and such a glomerular injury with reduced podocyte count was associated with proteinuria (Chitra et al, ; Nishad, Nakuluri, Motrapu, & Pasupulati, ). To investigate whether the observed proteinuria and decreased podocyte count in rats exposed to hypoxia were owing to podocyte injury, we then investigated the effect of hypoxia on human immortalized podocytes.…”
Section: Resultsmentioning
confidence: 99%
“…Besides the loss of E‐ and P‐cadherin expression, several other proteins are also deregulated during EMT of podocytes including nephrin and podocin (Nishad et al, ). We found attenuated expression of ZO‐1 and increased expression of N‐cadherin, β‐catenin, and vimentin in rats exposed to hypoxia.…”
Section: Discussionmentioning
confidence: 99%
“…The EMT is a critical mechanism in physiological and pathological processes, such as embryogenesis, wound healing, and cancer development, enabling cells to transit from an epithelial to a mesenchymal state [ 59 ]. The literature defines three distinct EMT subtypes, each of which occurs in different biological circumstances and has a range of functional outcomes [ 60 , 61 ].…”
Section: Infiltration and Invasion Of Gbm Cellsmentioning
confidence: 99%
“…Injury to the podocyte is an important cause of several glomerular diseases. One of the responses of podocytes to various injuries is EMT which results in depletion of these cells leading to heavy proteinuria [5]. The phenotypic switch seen in the podocytes closely resembles type II EMT [6].…”
Section: Podocyte Epithelial-mesenchymal Transitionmentioning
confidence: 99%